Overview of pharmacoeconomic modelling methods - Ademi, Z.; Kim, H.; Zomer, E.; Reid, Christopher; Hollingsworth, B.; Liew, D. (2013)
In the current climate of burgeoning health care costs, pharmacoeconomics is becoming increasingly important, but knowledge about pharmacoeconomic methods is limited among most clinicians. This review provides an introduction to, and overview of, common methods used in pharmacoeconomic modelling: decision analysis, Markov modelling, discounting and uncertainty analyses via Monte Carlo simulation. It will conclude with a suggested approach to reading and appraising published pharmacoeconomic analyses. © 2012 The British Pharmacological Society.